1992
DOI: 10.1007/bf02393829
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting overall satisfaction with a river recreation experience

Abstract: ABSTRACT/Visitor satisfaction has been a consistently stated goal of outdoor recreation management. Recreation resource managers provide opportunities for the visiting public with the anticipation of satisfying the needs of the visitors. Management efforts are often evaluated in terms of visitor satisfaction. In the recent decade, a multiple satisfactions approach has been the primary research paradigm guiding visitor satisfaction research. This paradigm has focused primarily upon behavioral-type dimensions su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 4 publications
2
28
0
Order By: Relevance
“…These findings are supported by Herrick and McDonald (1992) who suggested that visitors use setting attributes to evaluate their overall satisfaction. The importance of the experience dimensions to overall satisfaction emphasizes the fact that visitors specifically seek experiences relating to artifactualism, naturalness, remoteness and solitude when hiking in natural areas.…”
Section: User Satisfactionsupporting
confidence: 54%
See 1 more Smart Citation
“…These findings are supported by Herrick and McDonald (1992) who suggested that visitors use setting attributes to evaluate their overall satisfaction. The importance of the experience dimensions to overall satisfaction emphasizes the fact that visitors specifically seek experiences relating to artifactualism, naturalness, remoteness and solitude when hiking in natural areas.…”
Section: User Satisfactionsupporting
confidence: 54%
“…goal attainment) and setting attributes (e.g. facility development and resource impacts) (Herrick and McDonald, 1992). Understanding recreational satisfaction can help managers and planners to understand the types of opportunities visitors are seeking, and to develop services that help enhance those desired experiences (Buchanan, 1983).…”
Section: Methodsmentioning
confidence: 99%
“…It was known that guest satisfaction can be proper when the performance of various attributes due to a product or service [3]. Choi [4] states that overall customer satisfaction consists of multiple dimension of a product or service in various hospitality areas including tourism [5]- [7]. In India, from recent era, tourism and hospitality industry provides employment generation in local people as well as revenue generation through foreign exchange [8].…”
Section: Introductionmentioning
confidence: 99%
“…Situational variables involve specific attributes of a recreational setting/activity; these include the absence of litter and other pollution, level of facility development, pleasant social demeanour of others, and good physical condition of the site. Subjective variables include perceptions of crowding, the extent to which participation goals were fulfilled, and perceptions of impact (Herrick & McDonald, 1992). Subjective variables may have more direct and powerful influences on overall 34 satisfaction with non-consumptive recreation activities, but are strongly correlated to situational variables (Whisman & Hollenhorst, 1998 (Latu & Everett, 2000).…”
Section: Visitor Satisfaction Researchmentioning
confidence: 99%
“…Although some researchers measure total satisfaction by asking visitors to provide an overall rating of experience quality (Stewart & Cole, 1999), this is sometimes viewed as an inadequate measure due to its extremely broad nature (Manning, 1999;Herrick & McDonald, 1992;Latu & Everett, 2000). Approaching satisfaction associated with the recreation experience as a function of all-encompassing multiple and independent aspects can be more accurate (Herrick & McDonald, 1992;Latu & Everett, 2000;Orams 2000;Whisman & Hollenhorst, 1998). This can be done through the use of multiple-item scales that measure satisfaction with specific aspects of the recreation experience (Manning, 1999).…”
Section: Visitor Satisfaction Researchmentioning
confidence: 99%